Website-based final project management system design at Trisakti university industrial engineering - Ratna Mira Yojana; Elfira Febriani Harahap; Winnie Septiani; Sucipto Adisuwiryo; Ewaldo Brata (Universitas Serang Raya, 2022)
Preparing the final project is one of the requirements for graduation from a college student. The right Final Project management system will affect the quality of education. Industrial Engineering Trisakti University is one of the leading universities in Indonesia that continues to develop its education system. Managing the final project at Trisakti University Industrial Engineering is still manual and has not been integrated. As a result, the risk of errors in entering and saving Final Project data is still high. Therefore, this research was conducted to design a final project management system at Trisakti University Industrial Engineering. It begins with analyzing the existing management system. It is described with swim lane diagrams and PIECES to determine the process flow in the system and the actors who play a role in the system. After analyzing the system, proceed with designing information systems with Object-Oriented Modeling and evaluate it with black box testing and ERRC. This research results in website-based final project management at Trisakti University Industrial Engineering.